An Analysis of Macronutrient Dietary Diversity and the Desirable Dietary Pattern Score (DDP Score) in Urban Regions of West Kalimantan - Fadly, Dzul (Media Publikasi Cendekia Indonesia, 2025)
Food consumption diversity is an important indicator for assessing the quality of people's diets, especially in the context of urbanization, which affects preferences and access to different types of food. The imbalance of macronutrient consumption, such as the dominance of carbohydrates and low intake of protein and fat, is a public health challenge in Indonesia, including the West Kalimantan region. This study aimed to analyze macronutrient consumption and evaluate the Desirable Dietary Pattern (DDP) score of people in urban areas of West Kalimantan in 2023. This study used a descriptive quantitative approach involving 200 households in Pontianak and Singkawang cities. Data were collected through a food consumption survey and analyzed based on the average consumption of energy, protein, fat, and carbohydrates, as well as the DDP score. The results showed that the average energy and protein consumption in both cities were relatively similar, at approximately 1900 Kcal and 50 Kcal/capita/day, respectively. However, there were significant differences in fat and carbohydrate consumption, with Pontianak recording higher values. The DDP scores were good, at 89.7 in Pontianak and 86.8 in Singkawang. However, there are still inequalities in consumption between food groups, especially the low consumption of oily fruits/seeds, tubers, and nuts. In conclusion, although the energy consumption and food diversity of the community are relatively good, improvements are needed in the distribution of consumption between food groups to support a more balanced and sustainable diet for the community.